Mifepristone inhibited the expression of B7-H2, B7-H3, B7-H4 and PD-L2 in adenomyosis - Xiaoyan Qin; Wenjing Sun; Chong Wang; Mingjiang Li; Xingbo Zhao; Changzhong Li; Hui Zhang (BMC, 2021)
Abstract Background The immune mechanism was shown to be involved in the development of adenomyosis. The aim of the current study was to evaluate the expression of the immune checkpoints B7-H2, B7-H3, B7-H4 and PD-L2 in adenomyosis and to explore the effect of mifepristone on the expression of these immune checkpoints. Methods The expression of B7-H2, B7-H3, B7-H4 and PD-L2 in normal endometria and adenomyosis patient samples treated with or without mifepristone was determined by immunohistochemistry analysis. Results In adenomyosis patient samples, the expression of B7-H2, B7-H3 and B7-H4 was increased in the eutopic and ectopic endometria compared with normal endometria, both in the proliferative and secretory phases. Moreover, the expression of B7-H2 and B7-H3 was higher in adenomyotic lesions than in the corresponding eutopic endometria, both in the proliferative and secretory phases. The expression of PD-L2 was higher in adenomyotic lesions than in normal endometria in both the proliferative and secretory phases. In the secretory phase but not the proliferative phase, the expression of B7-H4 and PD-L2 in adenomyotic lesions was significantly higher than that in the corresponding eutopic endometria. In normal endometria and eutopic endometria, the expression of B7-H4 was elevated in the proliferative phase compared with that in the secretory phase, while in the ectopic endometria, B7-H4 expression was decreased in the proliferative phase compared with the secretory phase. In addition, the expression of B7-H2, B7-H3, B7-H4 and PD-L2 was significantly decreased in adenomyosis tissues after treatment with mifepristone. Conclusions The expression of the immune checkpoint proteins B7-H2, B7-H3, B7-H4 and PD-L2 is upregulated in adenomyosis tissues and is downregulated with mifepristone treatment. The data suggest that B7 immunomodulatory molecules are involved in the pathophysiology of adenomyosis.